IAEA survey of dental cone beam computed tomography practice and related patient exposure in nine Central and Eastern European countries - Beganović, Adnan; Ciraj-Bjelac, Olivera; Dyakov, Iliya; Gershan, Vesna; Kralik, Ivana; Milatović, Aleksandra; Šalát, Dušan; Stepanyan, Karapet; Vladimirov, Anatoli; Vassileva, Jenia (British Institute of Radiology, 2019)
Cone beam CT (CBCT) in dentistry and maxillofacial surgery is a widely used imaging method for the assessment of various maxillofacial and dental pathological conditions. The objective of this study was to summarize the results of a multinational retrospective-prospective study that focused on patient exposure in this modality.
Keywords: Cone-Beam Computed Tomography, Dental Radiography, Patient Dose, Radiation Exposure, Diagnostic Imaging